(untitled) (Economic and Political Thought, 2013)
The article shortly presents the silhouette and views of an Austrian-American political philosopher Eric Voegelin, who is not well known in Poland. Voegelin radically questioned the methods and practices used in the modern social sciences. The great development of exact sciences in the time of scientific revolution led to a belief that the methods used in those sciences can be successfully used in social sciences. In the course of time, the view eliminated other methods and acknowledged experience, inductive concluding and mathematical logics as the only acceptable methods in scientific research. Positivism made the methods the only criteria of scholarship and all the fields that did not use them were expelled from the area of science. According to Voegelin, science requires the use of such methods that are adequate to the nature of scientific examination (mathematics is for example not very useful in the analysis of The Republic by Plato). A man wants to know but does not get to know the reality as an external observer but as a participant. A man gets to know some fragments of the reality not in an empiric way but through internal consciousness and meditation. The history of humanity is a process of “attunement” of human cognition to the existing order of existence. The consciousness of a transcendental source of existence has always accompanied a man. Originally, a man finds a reflection of an existence order in a cosmological civilization. A leap in being towards the existing order takes place in Israel through revelation and finishes in Christianity. This makes a man give up a myth for the benefit of history. Science is to help in the attunement to the order of existence and its transcendental source.